Equally Public and Private Refugee Resettlement: The Historical Development of Canada’s Joint Assistance Sponsorship Program - McNally, Rachel (Refuge, 2023)
For over 40 years, Canada’s Joint Assistance Sponsorship Program has combined government financial assistance, professional settlement services, and private sponsor settlement support for refugees identified as having “special needs.” With high public and private involvement, the program offers another potential model for sponsorship, yet existing knowledge about the program is limited. This article explores the historical development of the program, highlighting three time periods: 1979–1981, when it launched; 1998–2001, when it welcomed thousands of Kosovars and expanded as selection criteria prioritized vulnerability; and 2014–2019, as it increasingly competed with other sponsorship programs.